Global Education Development Plan to Build Sustainable Education Based on Artificial Intelligence - Siti Marisa; Gunawan Gunawan; Evi Susilawati (Qubahan Academic Journal)
Global education is an important aspect in preparing a generation ready to face the challenges of the future. In an effort to develop sustainable education, the use of artificial intelligence is one of the interesting potentials to consider. The research aims to explain the design of global education development aimed at developing AI-based sustainable education through library studies. The study uses a library study method by collecting, analysing, and synthesizing research, scientific articles, reports, and other relevant literary sources. The research focuses on three important aspects in the design of AI-based global sustainable education development, namely, learning personalization, adaptive curriculum development, and student progress assessment and monitoring. The library study results show that the use of AI in education can enable more effective learning personalization. With AI, learning materials can be tailored to individual student needs and preferences, enhancing their engagement and understanding. Furthermore, AI-supported adaptative curricular development allows learning experiences that are adapted to student development and capabilities. Student progress evaluation and surveillance can also be enhanced through the application of AI. This technology can provide more objective and comprehensive assessment of student progress, helping teachers to provide more timely feedback and support better decision-making in learning planning. While the potential for the use of AI in sustainable global education is promising, there are challenges and consequences to bear in mind. Ethical aspects, student data privacy, and fairness in access and use of AI technology should be key concerns in designing sustainable global education development. The study provides insight into the design of AI-based sustainable global education development through library studies. These findings could provide a basis for further research and provide practical guidance to stakeholders in adopting and implementing AI technologies responsibly to develop sustainable education at a global level.